2001
DOI: 10.1002/hup.333
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic promise of single enantiomers: introduction

Abstract: This review uses several examples drawn from the literature to show how using active enantiomers as therapeutic agents may yield several benefits, including more predictable pharmacokinetics, more accurate drug monitoring and enhanced tolerability. As a result of these benefits, the therapeutic use of single enantiomers will become increasingly important not only in psychopharmacology, but in medicine generally. Indeed, over the early years of the new millennium, the therapeutic use of single active enantiomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…As a result of strong grass root movements that started and flourished in the whole of 1980s, the thinking towards chirality aspects and their likely impact on therapeutic outcome and redefining the benefit-risk potential of enantiomers vs racemate, via chiral switches, has taken a front seat. Now it is well understood that the therapeutic dilemma posed by the use of racemic drugs is largely due to the differences in interactions between individual enantiomers and the asymmetric environment of the biological systems (Ariens, 1984;Hutt and O'Grady, 1996;Wainer, 2001;Benedetti et al, 2002;Baumann et al, 2002). As a direct consequence, the enantiomers have been observed to demonstrate disparities in the respective pharmacological, pharmacokinetic, pharmacodynamic and toxicological properties (Drayer, 1986;Jamali et al, 1989;Rentsch, 2002;Srinivas, 2001).…”
mentioning
confidence: 99%
“…As a result of strong grass root movements that started and flourished in the whole of 1980s, the thinking towards chirality aspects and their likely impact on therapeutic outcome and redefining the benefit-risk potential of enantiomers vs racemate, via chiral switches, has taken a front seat. Now it is well understood that the therapeutic dilemma posed by the use of racemic drugs is largely due to the differences in interactions between individual enantiomers and the asymmetric environment of the biological systems (Ariens, 1984;Hutt and O'Grady, 1996;Wainer, 2001;Benedetti et al, 2002;Baumann et al, 2002). As a direct consequence, the enantiomers have been observed to demonstrate disparities in the respective pharmacological, pharmacokinetic, pharmacodynamic and toxicological properties (Drayer, 1986;Jamali et al, 1989;Rentsch, 2002;Srinivas, 2001).…”
mentioning
confidence: 99%
“…Our study identified RCTs favoring a single-enantiomer drug over its racemic precursor based on any safety end point for only 3 of 15 drugs, and differences were often observed for a single adverse event or vital sign without clear clinical relevance. Benefits claimed with chiral switching often revolve around safety, 5 , 14 and previous reviews relying on preclinical evidence or trials in healthy volunteers have suggested that single-enantiomer drugs are safer than racemic drugs. 12 , 25 , 26 For example, according to animal studies and trials in healthy volunteers, levobupivacaine, which accounted for two-thirds of identified RCTs, was believed to pose less risk of cardiac and central nervous system toxicity than its precursor, bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“… 3 However, the suggested benefits of single-enantiomer drugs are often based on nonclinical trial evidence, such as in vitro and animal studies. 3 , 5 , 12 , 13 , 14 Moreover, manufacturers of single-enantiomer drugs are not required to conduct randomized clinical trials (RCTs) directly comparing their products with existing racemic drugs before receiving FDA approval. 15 , 16 , 17 Between 2001 and 2011, only one-third of approvals of single-enantiomer drugs with racemic precursors were based on RCTs directly comparing the 2 drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of indacrinone which is used in the treatment of hypertension and congestive heart failure, the free fractions are 0.9% and 0.3% for the (R)-and (S)-enantiomer respectively [130].…”
Section: Ix)mentioning
confidence: 99%